Electro-Oxidation of Methanol at Copper and Nickel Modified Clay Electrodes (Global Journal of Science Frontier Research, 2015)
Cu/Clay/316L and Ni/Clay/316L anodes were prepared by the electroplating of a Cu and Ni catalyst layer onto Clay/Stainless Steel plates for a direct methanol fuel cell (DMFC). The morphology and structure of the catalyst layers were analyzed by AFM and Optical microscopy. The catalyst coating layer shows an alloy character. The results show that oxides formation at the electrode surface is necessary for the methanol oxidation.
Keywords: modified electrodes; catalyst; DMFC; square wave voltammetry